2009
DOI: 10.15517/rbt.v59i1.3184
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo reproductivo del ostión de manglar Crassostrea rhizophorae (Bivalvia: Ostreidae) en la Bahía de Camamu, Bahia, Brasil

Abstract: Reproductive cycle of the mangrove oyster Crassostrea rhizophorae (Bivalvia: Ostreidae) in Camamu Bay, Bahia, Brasil. The mangrove oyster Crassostrea rhizophorae is important fishery resource along the entire Brasilian coast with excellent potential for marine culture. The purpose of this paper was to examine the reproductive characteristics of the oyster of the Maraú river estuary in Camamu Bay, Bahia, Brasil. The samples were collected monthly, from September 2006 to August 2007, at two points (I and II) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
14
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 11 publications
9
14
1
2
Order By: Relevance
“…This finding is similar to that reported by several authors in oysters of the genus Crassostrea (Rodríguez-Jaramillo et al, 2008;Lenz & Boehs, 2011). The age and size of the (Vélez, 1991).…”
Section: __________________supporting
confidence: 91%
See 1 more Smart Citation
“…This finding is similar to that reported by several authors in oysters of the genus Crassostrea (Rodríguez-Jaramillo et al, 2008;Lenz & Boehs, 2011). The age and size of the (Vélez, 1991).…”
Section: __________________supporting
confidence: 91%
“…In this work, it was found a 1.3% hermaphroditic specimens in May, which is the month of greatest reproductive activity for C. corteziensis, at La Palicienta Lagoon. The proportion of hermaphrodites (1.5%) is similar to that reported for this species in other areas of distribution (Chávez- et al, 2003), and C. rhizophorae (0.8 to 1.3%) (Lenz & Boehs, 2011). These authors attribute hermaphroditism to the age of specimens and to environmental stimuli; however, Paniagua-Chávez & Acosta-Ruíz (1995) attributed this to the fact that in hermaphroditism, complete removal and reabsorption of gametes of the most recent reproductive cycle and new gametogenesis do not occur.…”
Section: __________________supporting
confidence: 87%
“…The incidence of hermaphrodites in a population of C. brasiliana was 0.6% (Galvão et al, 2000). Comparable results were reported by Nascimento (1978) and by Lenz and Boehs (2011), who reported low incidence rates of 0.52 and 0.76%, respectively, for hermaphroditic C. rhizophorae. Shpigel (1989) observed that the males of C. gigas and Ostrea edulis (Linnaeus, 1758) become mature earlier than the females.…”
Section: Field Experimentssupporting
confidence: 76%
“…Partial spawns, followed by a recovery phase, are more frequent throughout the year. Lenz and Boehs (2011) studied the reproductive biology of C. rhizophorae in two environments in the Bay of Camamu (BA) and found that these oysters were in different stages of the reproductive cycle throughout the year. It is likely that the reproductive cycle of oysters in these regions is less subject to seasonal influences than it would be in the South and Southeast, where the oysters would be more susceptible to other environmental events, such as rainfall.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Information is available for Donax hanleyanus Philippi, 1847 (Gil and Tomé, 2004a), Chione pubera (Bory Saint-Vicent, 1827) (Borzone et al, 2001), Perna perna (Linnaeus, 1758) (Galvão et al, 2006), Anomalocardia brasiliana (Gmelin, 1791) (Narchi, 1976;Grotta and Lunetta, 1980;Barreira and Araújo, 2005;Luz and Boehs, 2011) and Crassostrea rhizophorae (Guilding, 1828) (Nascimento and Lunetta, 1978;Nascimento et al, 1980;Lenz and Boehs, 2011).…”
Section: Introductionmentioning
confidence: 99%